Current readiness on food fraud risk mitigation in developing countries: a review - Hafiz Muhammad Rizwan Abid; Sadia Aslam; Nisreen Alwan; Nauman Khalid (Agriculture & Food Security)
Abstract Food fraud is a deceptive act of deliberately and intentionally changing food composition for economic gain. In the context of developing countries, different emerging food fraud patterns are observed, including counterfeiting, dilution, substitution, mislabeling, etc. These have been proven to pose risks to people’s health in the past few years. Currently, most developing countries have a food fraud mitigation readiness status ranging from low to moderate. Weak regulatory frameworks, lack of enforcement, the socio-economic situation, and the surveillance system gaps are some of the major reasons for low to moderate risk mitigation readiness. This paper identifies the foods most susceptible to food fraud, and significant tool systems to mitigate food fraud are also indicated. Some developing countries implement regulatory reforms and adopt advanced detection technologies, but the enforcement is still inconsistent due to resource limitations. In addition, the lack of integrated watchdog surveillance and collaboration among different stakeholders hinders effective food fraud mitigation. This review evaluates the success of modern and traditional food fraud methods, especially concerning labeling practices. The issue of molecular forensics and new analytical methods are studied in terms of their contribution towards strengthening the detection and control of food fraud. The emphasis is on developing countries, where the application of these technologies needs to be put in place to improve readiness to mitigate the food fraud risk.